Comparative analysis of practices of development and scientific researches of tourism activities - Петренко, В. П.; Кісь, С. Я.; Ільницький, Д. Є. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article presents the results of tourist industry development in Ukraine within 2000- 2013, which prove the necessity to convey both practical and theoretical researches, aiming to enhance the impact of tourism on the country’s economy. The results of the theoretical investigations analysis in the sphere of tourism theory, recreation and tourism potential in Ukraine, economy and management of tourism helps formulate the proper interpretation of the definition "tourism", link categories "recreational potential" and "intellectual potential" as well as identify the concept "mediated economic befit of tourism".